Conceptual and measurement issues in poverty analysis - Erik Thorbecke (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
The objective of this paper is to review a number of issues related to poverty, while taking stock of the ongoing research. Most of the remaining unresolved issues in poverty analysis are related directly or indirectly to the dynamics of poverty. Before the development community can become more successful in designing and implementing poverty-alleviation strategies, within the context of growth, we need to understand better the conditions under which some households remain permanently (chronically) poor and how others move in and out of poverty. In what follows we review the state of the art under a number of interrelated headings: (1) Chronic vs. transient poverty; (2) Poverty and vulnerability; (3) The determination of the poverty line across time and countries; (4) The quantitative vs. qualitative approach to poverty measurement; and (5) Growth, inequality and poverty.
Keywords: I31; I32; 330; poverty; vulnerability; inequality; measuring human well-being; Armut; Messung; Theorie